Measurement of the pp̄→tt̄ production cross section and the top quark mass at s=1.96TeV in the all-hadronic decay mode - Aaltonen, T; Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2007)
We report the measurements of the tt̄ production cross section and of the top quark mass using 1.02fb-1 of pp̄ data collected with the CDF II detector at the Fermilab Tevatron. We select events with six or more jets on which a number of kinematical requirements are imposed by means of a neural network algorithm. At least one of these jets must be identified as initiated by a b-quark candidate by the reconstruction of a secondary vertex. The cross section is measured to be σtt̄=8.3±1.0(stat)-1.5+2.0(syst) ±0.5(lumi)pb, which is consistent with the standard model prediction. The top quark mass of 174.0±2.2(stat)±4.8(syst)GeV/c2 is derived from a likelihood fit incorporating reconstructed mass distributions representative of signal and background. © 2007 The American Physical Society.